Pengaruh Social Media Marketing Terhadap Purchase Decision Melalui Brand Awareness dan Electronic Word of Mouth - Berliani, Tiwi; Rojuaniah, Rojuaniah (Jurnal Ilmiah Wahana Pendidikan, 2023)
In today’s digital era, social media has important role in everyday life, one of which is as a digital marketing channel. Social media marketing can be utilized to increase brand awareness, sales, and company profits. This study aims to determine the effect of social media marketing on purchase decisions through brand awareness and electronic word of mouth. This research is a causal research with a quantitative method approach and uses the Structural Equation Modeling (SEM-PLS) analysis method. The population in this study are active social media users, following Somethinc's official social media accounts, have purchased Somethinc products, and live in Jabodetabek city aged 17 - 39 years. The sampling technique used purposive sampling technique with a total sample size of 236 respondents. The results of this study indicate that social media marketing has a positive effect on brand awareness, electronic word of mouth, and purchase decision. Brand awareness positively mediates social media marketing on purchase decision. Electronic word of mouth also positively mediates social media marketing on purchase decision. Based on these results, Somethinc is advised to improve marketing strategies that can make consumers talk more about their products on digital channels so that they can encourage purchase decisions.